2017
DOI: 10.4992/jjpsy.88.16216
|View full text |Cite
|
Sign up to set email alerts
|

Development of Japanese version of the Body Appreciation Scale-2

Abstract: Cathexis Scale を開発しており,日本においても当該 尺度を参考にして,身体満足度尺度(柴田, 1990)が 作成されている。また,Franzoi & Shields(1984)は 自己の身体の様々な側面をどの程度好んでいるかを測 定する Body Esteem Scale を開発した。さらに,Brown, Cash, & Mikulka (1990)は Multidimensional Body Self-Relations Questionnaire を開発しており,その appearance evaluation 下位尺度では,どの程度自分が外見的に魅力 的であると考えているかを測定することができる。た だし,これらの尺度は,個人の外見に対する満足度の み測定している。ポジティブボディイメージは,身体 満足感や外見への好意的な評価にとどまらぬ多次元的 概念である(Tylka & Wood-Barcalow, 2015b)ため,前 述の尺度はポジティブボディイメージの測定尺度とし ては不十分である。 上記のような尺度の存在を踏まえた上で,より包 括的なポジティブボディイメージ測定尺度であると 考 え… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…(2017), and Razmus and Razmus (2017) found no difference between men and women in 77 mainland China, Spain, and Poland respectively, most studies reported that men have 78 significantly higher body appreciation than women, with a small or moderate effect size, 79 Moreover, in order to compare the level of positive body image among different 97 cultures, it is essential to examine the cross-cultural equivalence of the BAS-2 (Swami, 98 García, et al, 2017). Even though the BAS-2 has been used among more than 10 culture 99 groups (e.g., Atari, 2016; Kertechian & Swami, 2017;Namatame et al, 2017), its cross-100 cultural measurement invariance has not been tested. Although the BAS-2 has been validated 101 in many countries, it has not been validated in Denmark, Portugal, and Sweden.…”
mentioning
confidence: 99%
“…(2017), and Razmus and Razmus (2017) found no difference between men and women in 77 mainland China, Spain, and Poland respectively, most studies reported that men have 78 significantly higher body appreciation than women, with a small or moderate effect size, 79 Moreover, in order to compare the level of positive body image among different 97 cultures, it is essential to examine the cross-cultural equivalence of the BAS-2 (Swami, 98 García, et al, 2017). Even though the BAS-2 has been used among more than 10 culture 99 groups (e.g., Atari, 2016; Kertechian & Swami, 2017;Namatame et al, 2017), its cross-100 cultural measurement invariance has not been tested. Although the BAS-2 has been validated 101 in many countries, it has not been validated in Denmark, Portugal, and Sweden.…”
mentioning
confidence: 99%
“…The Body Appreciation Scale-2 ( Tylka and Wood-Barcalow, 2015 ; Japanese version: Namatame et al, 2017 ) is a widely used 10-item questionnaire on positive body image. This is a revision of the original 13-item BAS ( Avalos et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…All participants completed the Japanese pencil-and-paper versions of the AQ ( Wakabayashi et al, 2004 ) and BAS-2 ( Namatame et al, 2017 ) tests after performing the visual hand recognition tasks. The items in the AQ (e.g., “It does not upset me when my daily routine is disturbed”) are answered on a 4-point Likert scale (“definitely agree,” “slightly agree,” “slightly disagree,” and “definitely disagree”), while the participants rated each item of the BAS-2 (e.g., “Despite its flaws, I accept my body for what it is”) to indicate whether the question was true about the participant’s approval and acceptance of their own body, noted on a 5-point scale (i.e., never = 1, seldom = 2, sometimes = 3, often = 4, and always = 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the results of EFA-based studies have shown that BAS-2 scores are one-dimensional in college samples from Hong Kong , Iran , the Netherlands , and the United Arab Emirates , as well as a community sample from Serbia (Jovic, Sforza, Jovanonic, & Jovic, 2017). Likewise, the results of CFAbased studies have shown adequate fit of the one-dimensional factor structure in a staff-andstudent sample from mainland China , college samples from France , Iran (Hosseini, Karimi, & Rabiei, 2018), Japan (Namatame, Uno, & Sawamiya, 2017), and Romania , adolescents from Denmark, Portugal, and Sweden , teachers from Turkey (Anlı, Akın, Eker, & Özcelik, 2015), older adults from Portugal , and community samples from Malaysia , Poland , and Spain .…”
Section: Introductionmentioning
confidence: 99%